Antibacterial Activity Test of Jackfruit Leaf Extract (Artocarpus heterophyllus Lam) against the Growth of Staphylococcus aureus Bacteria - Noventy Ratna Sari; Vicko Suswidiantoro; Wina Safutri; Riza Dwiningrum (CV. AFDIFAL MAJU BERKAH, 2025)
Jackfruit leaves (Artocarpus heterophyllus Lam) are tropical plants that grow widely in Indonesia. These leaves are known to contain phytochemical compounds, including tannins, flavonoids, and saponins, which have potential as antibacterial agents, including against Staphylococcus aureus. This study aims to determine the antibacterial activity of jackfruit leaf extract and to identify its effective concentration in inhibiting the growth of Staphylococcus aureus. The method used was experimental. The sample in this study was jackfruit leaf extract (Artocarpus heterophyllus Lam) with a yield of 16.74%. Phytochemical screening results indicated that the extract contained flavonoids, tannins, and saponins with antibacterial properties. The study was conducted using the disc diffusion method with five treatments and four replicates. The extract concentrations used were 40%, 60%, and 80%. The positive control used was 10 µg of the antibiotic ampicillin, while the negative control used 1% dimethyl sulfoxide (DMSO). The results of the study showed that a concentration of 40% produced an inhibition zone diameter of 7.12 mm (moderate category), a concentration of 60% produced 10.54 mm (moderate category), and a concentration of 80% produced 17.81 mm (strong category). The positive control produced an inhibition zone diameter of 7.55 mm (moderate category), while the negative control did not show any inhibition zone. Based on these results, it can be concluded that jackfruit leaf extract at a concentration of 80% is the most effective concentration as an antibacterial agent against Staphylococcus aureus, with a strong inhibition category based on the size of the inhibition zone formed.